A novel colchicine-myricetin heterozygous molecule: design, synthesis, and effective evaluations on the pathological models of acute lung injury in vitro and in vivo - Li, Zhiyue; Yan, Xueqin; Wei, Jiangchun; Pu, Liuyang; Zhu, Guanbao; Cao, Yongkai; Liu, Zhanyan; Liu, Yaqian; Li, Yan; Li, Limin; Li, Xinping; Wu, Zhengzhi (Frontiers in Pharmacology, 2023)
Acute lung injury (ALI) is an inflammatory condition and there are no effective treatments. A novel new compound----colchicine-myricetin hybrid (CMyrH) was herein designed and synthesized. To evaluate the activity of CMyrH in ALI, we used a bleomycin (BLM) induced BEAS-2B injury model in vitro and established a well-recognized rat model of BLM-induced lung injury in vivo. The results demonstrated that CMyrH protected BEAS-2B cells against BLM-induced cell injury in an increased dose manner, and reduced wet/dry weight ratio, histological scoring, and inflammation cytokines IL-1β, IL-6, IL-18, and TNF-α levels of lung tissue of the rats. Furthermore, we found CMyrH inhibited Caspase-1, ASC, GSDMD, and NLRP-3 expression in vivo. Meanwhile, we used molecular docking to analyze the binding mode of CMyrH and human neutrophil elastase (HNE), it revealed that CMyrH showed strong binding affinity toward HNE when compared to its parent molecules. In conclusion, It is suggested that CMyrH antagonized acute lung injury by focusing on multi-targets via multi-mechanisms, and may be served as a potential therapeutic agent for ALI.